Okulistyczna manifestacja choroby Creutzfeldta-Jakoba w wariancie Heidenhaina – opis przypadku - Linke, Anna; Cisiecki, Sławomir; Bonińska, Karolina; Bednarski, Maciej (Klinika Oczna / Acta Ophthalmologica Polonica, 2020)
We present the case of a 59-year-old female patient with the sporadic form of Creutzfeldt-Jakob disease in the Heidenhain variant. The main ocular symptoms were initial bilateral deteriorated visual acuity and final blindness. Due to a very low prevalence, non-specific symptoms and rapid course, making a quick and accurate diagnosis can be challenging. Vision impairment may occur in about 10% of patients with a sporadic form of Creutzfeldt-Jakob disease at the time of diagnosis and 50% during the disease. So far, no effective treatment has been found. The death of our patient occurred 9 weeks after the first symptoms.